Kinerja Beton High Volume Pofa - Ririn Yuari Farandia; Monita Olivia; Lita Darmayanti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The use of Palm Oil Fuel Ash (POFA) as a pozzolanic component in concrete continues in the future due to increase amount of POFA as by-product from industries annually. POFA is used as partial cement replacement in concrete and has significant impact on concrete’s performance. In this research, high volume POFA concrete with POFA replacement of 45%, 55% and 65% by cement mass were studied. POFA was obtained from local quarry in Riau Province. OPC concrete was used as control mix. Some properties namely workability, setting time, compressive strength, shrinkage and porosity were investigated. Results show that workability and compressive strength decreases as the POFA replacement increases in concrete. Porosity, shrinkage and setting time increases with an increase of POFA in concrete. It can be concluded high volume POFA using local material cannot improve the concrete performance significantly. Keywords: compressive strength, performance of concrete, POFA, porosity, pozzolans, shrinkage, setting times, workability